Using the Ruminant model to quantify methane emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The GHG Inventory compilers in Colombia are now using the Ruminant to quantify GHG emissions from the livestock sector which is a key GHG source category in Colombia.